Effectiveness of P5 Teaching Module Training at Al-Hakim Kalianda Kindergarten - Aradika, Muhammad Kahfi; Herpratiwi, Herpratiwi; Yulianti, Dwi; Rosidin, Undang (UNDIKMA, 2025)
The independent learning curriculum gives teachers the flexibility to create learning that is educational but also fun. The teaching module of the Pancasila Student Profile Strengthening Project (P5) is a teaching material designed to assist teachers in implementing Pancasila values in the learning process. the purpose of the study was to implement the P5 teaching module training at Al-Hakim Kids Kindergarten, South Lampung to determine the ability of teachers in the kindergarten. This research is a quantitative research with the aim of making a picture or descriptive of a situation objectively using numbers. The research involved 9 respondents using the P5 product that had been developed by the researcher to see the effectiveness of the product development. The results showed that the development carried out for four meetings resulted in 7 teachers getting a high category assessment while 2 were in the medium category, the observation results showed 82.8% interpreted the development product as very effective and interesting